HUBUNGAN PERSEPSI PERAWAT TENTANG PASIEN PERILAKU KEKERASAN DENGAN TINGKAT KECEMASAN PERAWAT DALAM MERAWAT PASIEN PERILAKU KEKERASAN - Afriani, Kartika; Nauli, Fathra Annis; Hasneli, Yesi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
A nurse in Mental Hospital that was treating patients at risk of violent behavior to accept violence from patients. Violent behavior exhibited by the patient in the from of verbal violence or physical violence, so it will give rise to a different perception on each nurse. In addition, it does not cover the possibility will arise a feeling fear and anxiety on the nurse when treatment for the patients of violent behavior. This research aimed to find out the correlation between the nurse perception about the violent behavior and their anxiety level in providing the treatment in Tampan Mental Hospital, Riau. The research used the correlative descriptive with cross sectional approach as the research design while the respondent was selected with using the total sampling techniques. The respondent of this research consist of 70 nurses. The researcher also used questionnaires which is related with the perception and the anxiety level of nurses to collect the data. After analyzed the data with using kolmogorof-smirnov test, the result shown that 0,233 as p value is bigger than 0,05 as alpha. Therefore, it can be concluded there is no correlation between the nurses perception about the patient with violent behavior and the anxiety level of nurses. Based on the research findings, add insights the nurses about are expected to capable in developing positive perspective and controlling their anxiety in order to provide the better treatment for the patients.Keywords : Anxiety, Perception, Violent Behavior